Pemanfaatan Media Sosial untuk Wirausaha Pariwisata - Faza Azka Asmara; Robertus saptoto; Putu Hardani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The use of social media has become one of the main strategies for enhancing the competitiveness of tourism entrepreneurship in the digital era. Platforms such as Instagram, TikTok, and YouTube are not only used as promotional tools but also as media for interaction, branding, and innovation in tourism services. This study aims to analyze how tourism entrepreneurs utilize social media to expand market reach, build destination image, and strengthen their competitive advantage. The research adopts a qualitative descriptive approach based on a literature review of various previous studies. The results show that digital literacy, content creativity, and branding strategies through social media contribute significantly to increasing the competitiveness and sustainability of tourism entrepreneurship.